Christian usage of the term "Allah" for god in the Malay Language : an analytical study - Ahmad Faizal bin Ramly (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
The controversy of the Christian usage of the term “Allah” to translate “God” (English) or “Eloah”, “El” and “Eloahim” (Hebrew) into the Malay language and the way it has been developed have upset both the Muslims and Christians alike. Many people who comment on this issue are not really clear about its comprehensive context, hence creating confusion and tension between the two religious communities, and even with the other communities in the nation too. This study examines the use of “Allah” by Christians in Malaysia in the context of Christian theological understanding compared with the usage of “Allah” in Islamic theology. Besides the theological aspect, this work also analyzes several arguments presented by both Christians and Muslims who agree or disagree with this usage. This study refers to printed materials such as books, original documents and other relevant materials. It also conducts interviews with the involved parties and makes references to their press statements. As the usage is on trial in court when the research is carried out, this study also uses Internet sources recommended by the concerned bodies, especially for the arguments of the Christians. The study finds that this issue has a very long historical root and it only reappears after an effort to mend the situation was initiated by the government. This study suggests that sensitive issues related to religions and the Constitution should be resolved through negotiations and inter-faith dialogues conducted by the academia, clerics and executive bodies and done with integrity and transparency to convince the public, rather than through the courts.